Legal Aspects of Cooperatives’ Issuance of Products to Non-Member Communities in Indonesia - Adristi, Dhia Novita; Gultom, Elisatris; Faisal, Pupung (Lentera Hukum, 2021)
Regulations of savings and loan cooperatives allow cooperatives to collect funds, resulting in the chance of issuing products to non-member communities. This study aimed to analyze the practice of issuing products to non-member communities by cooperatives. By highlighting the principle of membership as the specialty of cooperatives in Indonesia, it argued that issuing products to non-member communities is a deviation of cooperative's business activity. It accounted for the cooperative regulations, objectives, and principles of membership in cooperatives to the practice of issuing products to non-member communities that deviate from statutory regulations does not arise. The study used legal research derived from secondary data, among others primary legal materials, secondary legal materials, and tertiary legal materials. This study showed that the practice of issuing products to non-member communities is a deviation from statutory regulations, objectives, and membership principles in cooperatives. In the meantime, cooperatives while maintaining their identity requires all cooperative actors, the government, and the general public in preventing and following up on savings and loan cooperative practices that eliminate membership rights for service users. KEYWORDS: Cooperative Law, Cooperatives in Indonesia, Economic Democracy.